A cheap and efficient catalyst with ultra-high activity for reduction of 4-nitrophenol1. Issue 30 (14th August 2015) - Pan, Weicheng; Zhang, Shenghuan; He, Fei; Gai, Shili; Sun, Yanbo; Yang, Piaoping
<x xml:space="preserve">Abstract</x> Ni/SBA-15 catalyst with ultra-small particle size (7 nm), good dispersion, and ultra-high loading amount (57.4%) of Ni nanoparticles was prepared by a unique in situ thermal decomposition and reduction route. It exhibits excellent catalytic activity and stability for 4-nitrophenol reduction.